Global distribution prediction and ecological conservation of basking shark (Cetorhinus maximus) under integrated impacts - Runlong Sun; Kaiyu Liu; Wenhao Huang; Xiao Wang; Hongfei Zhuang; Zongling Wang; Zhaohui Zhang; Linlin Zhao (Global Ecology and Conservation)
Global climate change presents substantial threats to marine ecosystems, with particularly profound impacts on widely distributed migratory species. The basking shark (Cetorhinus maximus), the second-largest fish species, faces significant conservation challenges due to overfishing, habitat degradation, and climate change, necessitating urgent research to address knowledge gaps in its spatial distribution and interactions with changing marine environments. This study employs various environmental variables and distribution data to construct a global species distribution model for basking sharks, predicting their distribution patterns under current and future climate scenarios. The results indicate that chlorophyll, sea surface temperature, silicate and mixed layer depth are the primary factors determining habitat suitability for basking sharks. Under high-emission scenarios (Shared Socioeconomic Pathway, SSP5–8.5), our model predicts a shift toward the higher latitudes of the northern hemisphere in basking shark habitats, including temperate and sub-Arctic waters. Ecological corridor analysis identifies critical migratory pathways and pinch points, emphasizing the importance of incorporating the effects of climate change and human activities in the formulation of conservation strategies. The finding underscores the importance of integrated conservation strategies, highlighting how positive human interventions can aid in accurately identifying critical ecological corridors to ensure the long-term survival of the basking shark. Adaptive, science-based conservation measures are crucial to mitigating the effects of climate change and human activities, supporting the resilience of marine ecosystems.